2023
DOI: 10.1039/d3tc01737k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-intrinsic factors on pulse discharge and energy releasing performance of dielectric ceramics

Abstract: Power pulse ceramic capacitors are widely used in pulse generators and other fields because of their excellent charge and discharge performance. 0.55Bi0.5Na0.5TiO3-0.45Ba0.85Ca0.15Ti0.85Zr0.1Sn0.05O3(0.55NBT-0.45BCZTS) relaxor ferroelectric ceramics were manufactured by solid state...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Meanwhile, the characteristics of excessive mechanical rigidity also limit pp’s further application in the field of high-voltage power cables . Therefore, numerous studies have been performed to improve pp’s mechanical toughness, including elastomer blending , and polar functional groups grafting. , The above-mentioned modification method, which relies on the specific functions of additives to improve the properties of composites, is generally called nonintrinsic modification . The advantages of this method are functional diversity and strong operability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the characteristics of excessive mechanical rigidity also limit pp’s further application in the field of high-voltage power cables . Therefore, numerous studies have been performed to improve pp’s mechanical toughness, including elastomer blending , and polar functional groups grafting. , The above-mentioned modification method, which relies on the specific functions of additives to improve the properties of composites, is generally called nonintrinsic modification . The advantages of this method are functional diversity and strong operability.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The above-mentioned modification method, which relies on the specific functions of additives to improve the properties of composites, is generally called nonintrinsic modification. 20 The advantages of this method are functional diversity and strong operability. However, some studies have shown that the materials obtained by this modification method will appear agglomerated caused by phase separation, 21 as well as increased loss due to interfacial polarization under the effect of long-term electrothermal stress, 22 which will further result in the material's insulation degradation.…”
Section: Introductionmentioning
confidence: 99%